Perkembangan Motorik Siswa SD melalui Aktivitas Bulu Tangkis - Suhailah Haya Nasution; Ananda Putri Humayroh; Dhea Ananda Br Barus; Siti Afiqa Rahmah Manik; Fajar Siddiq (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This study aims to understand the motor development of elementary school students. The method used in this research is a qualitative descriptive approach, specifically a literature review. The purpose of this method is to describe the researcher's findings from several journal articles. This study examines how the motor development of elementary school students is influenced by badminton activities. Several journal analyses were used to collect data. Data analysis involved editing, drawing conclusions, and presenting the findings. The primary issue is analyzing children's development through the sport of badminton.